Pyrolytic transformation of indigenous biomass wastes into biochar: an insight into char structure and physicochemical characteristics - Nivya Mariam Paul; Variampally Sankar Harikumar (Journal of Agriculture and Rural Development in the Tropics and Subtropics, 2022)
Biochar, the product obtained by the pyrolysis of organic materials with little or no available air, acts as a long-term recalcitrant source of organic carbon when applied to soil. In the present study an in-farm method has been standardized for the pyrolytic conversion of four indigenous biomass resources into biochar. The biomass feedstocks viz. bovine bone (BB), coconut shell (CS), rubberwood (RW) and water hyacinth (WH) were dried and subjected to proximate, ultimate, biochemical analysis and were subjected to slow pyrolysis (563oC). The biomass feedstocks showed an ash content ranging from 1.04-61.23%, moisture content of 8.46-20.83%, volatile matter of 27.92-74.92% and fixed carbon of 1.17-18.75%. The biochar yield was maximum for BB (56.65%). Scanning electron microscope analysis of the biochar samples showed aligned honeycomb like groups with the greatest porosity (3.90-8.43 µm) in WH biochar. X-ray spectroscopy (EDX) analysis showed highest number of elements in WH biochar. The electrical conductivity, bulk density and water holding capacity of the biochars ranged from 102.56-7569.03 µs cm-1, 16.83-72.58 g cm-3 and 57.89-431.17%, respectively. The Fourier Transform Infrared spectrometer (FTIR) analysis of biochar samples showed several functional groups which help them to act as a good soil conditioner. Characteristics of the biochar produced from these biomass wastes revealed its potential as good soil conditioners in crop production systems.